2014
DOI: 10.1245/s10434-014-4211-7
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel Lymph Node Biopsy in Thick-Melanoma Patients (N=350): What is Its Prognostic Role?

Abstract: We confirmed that thick-melanoma patients are a heterogeneous group with different prognosis. In our experience, SLNB allowed for an appropriate stratification of patients in different survival groups. On the basis of our results, we strongly recommend the routine execution of SLNB in cases of primary melanoma thicker than 4 mm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 31 publications
(46 reference statements)
3
42
0
2
Order By: Relevance
“…The prognosis of melanoma patients is dependent on clinical and pathological features including Breslow thickness, ulceration, SLN status, tumour mitotic rate, primary site, patient age, and sex [8,13,21,23] . Noteworthy, among the anatomic sites, the trunk is the one associated with the worse prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis of melanoma patients is dependent on clinical and pathological features including Breslow thickness, ulceration, SLN status, tumour mitotic rate, primary site, patient age, and sex [8,13,21,23] . Noteworthy, among the anatomic sites, the trunk is the one associated with the worse prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…10 Using immunostaining for D2-40, Peterson et al found LVI in 23% of 74 invasive melanomas. 9 Our double staining for D2-40/MITF1 method showed the highest LVI detection rate to date (38%). Taken together, these findings confirm that LVI is underestimated by H&E alone, and that immunohistochemistry is an essential ancillary diagnostic tool for LVI.…”
Section: Detectionmentioning
confidence: 70%
“…1,11,17 Previously, we showed that OS and disease-specific survival durations were shorter for patients with LVI than for those without LVI, and that immunostaining-detected LVI and ulceration were associated significantly with OS. 9 Rose et al 11 found that immunostaining-detected LVI was a significant marker of both reduced DFS and OS. Xu et al 17 found that LVI was associated significantly with time to regional nodal metastatic disease, time to first metastasis, and melanomaspecific death.…”
Section: Survival Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Melanoma patients with intermediate and thick tumours are offered a sentinel node biopsy to identify lymph node spread as this procedure has prognostic value stratifying patients in different risk categories [31,32,33]. Other parameters such as mitoses and ulceration are also helpful in thinner melanomas [34].…”
Section: What Is New In the Treatment Of Cutaneous Melanoma?mentioning
confidence: 99%